Comparison of most‐to‐least to error correction for teaching receptive labelling for two children diagnosed with autism. Issue 4 (23rd April 2014) - Leaf, Justin B.; Alcalay, Aditt; Leaf, Jeremy A.; Tsuji, Kathleen; Kassardjian, Alyne; Dale, Stephanie; McEachin, John; Taubman, Mitchell; Leaf, Ronald
Abstract : Prompting systems are guidelines of when to provide learners with prompts and when to fade prompts. Today, there are several prompting systems implemented to teach receptive labeling to individuals diagnosed with autism spectrum disorders and other disabilities. This study compared most‐to‐least prompting to an error correction procedure involving feedback and remedial trials for teaching two children with autism a variety of receptive labels. All teaching was implemented in a one‐to‐one instructional setting. Researchers taught each participant how to receptively identify 18 pictures; nine were taught using error correction and nine were taught using most‐to‐least. The researchers utilized an adapted alternating treatment design nested into a multiple probe design to evaluate the two procedures. Results indicated that participants were able to reach mastery criterion on 100% of skills taught using the error correction and were able to reach mastery criterion on 88.9% of skills taught using most‐to‐least. Additionally, error correction tended to require fewer trials for participants to reach mastery criterion.